The need for systematic approach to empower resilience among the disadvantage: a narrative review - Azman, Ahmad Zaid Fattah; M Sherif, Yosra Mohamed (PICCWED, 2024)
The concept of resilience is widely recognized as a critical factor in overcoming adversity and achieving one's full potential. This is particularly important for disadvantaged groups, such as people with disabilities, the elderly, women, and children, who often face more significant challenges than the general population. The poster highlights the importance of resilience in empowering vulnerable groups, with a focus on people with disabilities. It critiques the individual-centric approach to resilience and advocates for systemic changes. The study adopts a mixed-methods approach, combining qualitative insights from existing literature on resilience, particularly in the context of people with disabilities, with an analysis of current infrastructural and societal barriers. The findings suggest that while individuals with disabilities often exhibit remarkable resilience, their ability to thrive is significantly influenced by the accessibility and inclusiveness of their environment. The poster concludes that resilience is a crucial attribute for overcoming adversity, but it should not be viewed in isolation. The empowerment of vulnerable groups, especially people with disabilities, requires a shift from an individual-centric approach to resilience to one that encompasses systemic changes. By enhancing infrastructure and fostering inclusive societal attitudes, we can create an environment that truly supports the resilience and empowerment of all individuals, allowing them to reach their full potential.